2021
DOI: 10.1038/s41598-021-89180-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum SDMA and ADMA at hospital admission predict in-hospital mortality of COVID-19 patients

Abstract: COVID-19 is a disease with a variable clinical course ranging from mild symptoms to critical illness, organ failure, and death. Prospective biomarkers may help to predict the severity of an individual’s clinical course and mortality risk. We analyzed asymmetric (ADMA) and symmetric dimethylarginine (SDMA) in blood samples from 31 patients hospitalized for COVID-19. We calculated associations of ADMA and SDMA with mortality and organ failure, and we developed a predictive algorithm based upon these biomarkers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
4
19
2
Order By: Relevance
“…For metabolites including glutamine, glutamate, dimethylarginines, kynurenine, tryptophan, and phenylalanine, observations were in line with studies in patients with critical illness and sepsis [32][33][34][35][36][37][38][39][40], respiratory conditions (COPD, asthma, and ARDS) [41][42][43], bacterial pneumonia [44], and HIV-AIDS [45][46][47]. Similar differences in individual metabolites were reported in other studies comparing patients at varying COVID-19 stages, and those are indicated in Figure 6 per metabolite [21][22][23][24][25]27,30,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Although sporadic, the common findings highlight a consistency in the field despite the highly varied cohort characteristics, technical, and statistical approaches.…”
Section: Discussionsupporting
confidence: 87%
“…For metabolites including glutamine, glutamate, dimethylarginines, kynurenine, tryptophan, and phenylalanine, observations were in line with studies in patients with critical illness and sepsis [32][33][34][35][36][37][38][39][40], respiratory conditions (COPD, asthma, and ARDS) [41][42][43], bacterial pneumonia [44], and HIV-AIDS [45][46][47]. Similar differences in individual metabolites were reported in other studies comparing patients at varying COVID-19 stages, and those are indicated in Figure 6 per metabolite [21][22][23][24][25]27,30,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Although sporadic, the common findings highlight a consistency in the field despite the highly varied cohort characteristics, technical, and statistical approaches.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, capillary changes have been observed more frequently in post-COVID-19 patients compared to healthy controls and the group of ASCVD including also a higher MES. Changes for most of the respective parameters have previously been described in patients mainly with acute COVID-19 while data about persistent changes after suffered COVID-19 are very limited (9,(35)(36)(37)(38)(39)(40). Pathophysiological mechanisms contributing to endothelial dysfunction in COVID-19 are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength of our study is that we included a healthy control and a sex-and age-matched ASCVD control group to discriminate the impact of COVID-19 on endothelial dysfunction and inflammatory vasculopathy, which has not been done before in studies investigating endothelial function in people who had COVID-19. In previous studies, different COVID-19 phenotypes and COVID-19 subjects with several cardiovascular comorbidities were commonly included (9,(34)(35)(36)(37)(38)(39). A further strength is that all controls had no proven recent or prior SARS-CoV-2 infection at study measurement.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Recent interest has focussed on the role of pulmonary vascular damage and endothelial dysfunction in COVID-19 pneumonia and ensuing hypoxaemia and organ failure ( 69 , 70 ). We have reported that high ADMA and SDMA serum levels are superior biomarkers to predict COVID-19-associated in-hospital mortality ( 71 ), suggesting that NO deficiency may aggravate pulmonary and systemic vascular dysfunction in this disease. Accordingly, several small trials investigated the effects of inhaled NO ( 72 , 73 ) or the phosphodiesterase V inhibitor sildenafil on COVID-19-associated hypoxaemia and outcome ( 74 ).…”
Section: Clinical Relevance Of Hypoxic Pulmonary Vasoconstrictionmentioning
confidence: 99%